2020
DOI: 10.1177/0218492320947586
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair for infective endocarditis: Kobe experience

Abstract: Objectives We retrospectively analyzed our experience of mitral valve repair for native mitral valve endocarditis in a single institution. Methods From January 1991 to October 2011, 171 consecutive patients underwent surgery for infective endocarditis. Of these, 147 (86%) had mitral valve repair. At the time of surgery, 98 patients had healed (group A) and 49 had active infective endocarditis (group B). Repair procedures included resection of all infected tissue and thick restricted post-infection tissue, leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…De Kerchove et al 32 used repair‐oriented surgical methods, such as no‐patch techniques including triangular or quadrangular resection, sliding plasty, neochordae, and chordal transfer; patch techniques including pericardium, tricuspid autografting, the flip‐over technique, and partial mitral valve homografting; ring annuloplasty; and pericardial banding, which achieved a reparability rate of 80%. Okada et al 33 reported their experience in MVP for IE from 1991 to 2011, including a total of 147 patients who underwent repair procedures. These authors concluded that repair was very successful using autologous pericardium, ePTFE sutures, and ring annuloplasty, with a 10‐year survival rate of 88.5 ± 3.5%, a 5‐year freedom from reoperation rate of 99 ± 1.0%, and a freedom from valve‐related events rate of 94.4 ± 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…De Kerchove et al 32 used repair‐oriented surgical methods, such as no‐patch techniques including triangular or quadrangular resection, sliding plasty, neochordae, and chordal transfer; patch techniques including pericardium, tricuspid autografting, the flip‐over technique, and partial mitral valve homografting; ring annuloplasty; and pericardial banding, which achieved a reparability rate of 80%. Okada et al 33 reported their experience in MVP for IE from 1991 to 2011, including a total of 147 patients who underwent repair procedures. These authors concluded that repair was very successful using autologous pericardium, ePTFE sutures, and ring annuloplasty, with a 10‐year survival rate of 88.5 ± 3.5%, a 5‐year freedom from reoperation rate of 99 ± 1.0%, and a freedom from valve‐related events rate of 94.4 ± 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies reporting a superior overall survival of mitral valve repair (MVR) techniques over replacement, [3][4][5][6] this approach might be limited or not feasible when a large amount of mitral tissue needs to be resected or, even worse, is lacking, thus limiting the reparability or increasing the complexity of the repair. In this scenario, concerns have been raised about durability of the repair, especially in technically challenging cases.…”
Section: Introductionmentioning
confidence: 99%
“…Valvular plastic surgery can provide better long-term survival and improved heart performance compared to valve replacement [5]. The right time for patients to undergo a correction is a matter of discussion, and the current tendency is to shorten the diagnosis-surgery period [7][8][9][10]. The present patient had a problem because she was under 18 years of age.…”
Section: Discussionmentioning
confidence: 78%